A novel screw-type pyrolysis system for selectively producing value-added chemicals from lignocellulosic biomass - Altundogan, H. Soner; Tanyildizi, M. Saban; Kalender, Mehmet; Elcicek, Serhat; Pehlivan, Dursun (Springer Heidelberg, 2025)
In this study, a new unique screw-type (auger) reactor system was developed to selectively obtain valuable chemical-enriched liquid pyrolysis products. The new design has heating segments with increased temperature along the reactor tube and three-staged fractional condensing lines following pyrolysis gas ports at the end of each heating segment. To maximize liquid product yield, the effects of some parameters such as feeding rate, screw rate, and temperature profile were studied by the experiments designed with Response Surface Methodology (RSM). By fixing the maximum temperature at the last heating segment of a tubular reactor to 550 degrees C, the conditions for maximum liquid product yield were determined as feeder driver frequency of 21 Hz (13.6 rpm), auger driver frequency of 36 Hz (24.3 rpm), and Delta T (temperature difference between consecutive heating segments) of 66 degrees C. Biomass feeding rate and volumetric fullness ratio of the reactor at these conditions were 42 g min-1 and 0.58 (v/v), respectively. Under these conditions, total liquid, solid, and gas product yields were obtained as 57%, 19%, and 24%, respectively. In addition, analyses of the liquid fractions showed that valuable chemicals could be obtained selectively in a large extent by using the new design.
Keywords: Biomass pyrolysis; Staged degasification; Fractional condensation; Auger reactor; Levoglucosan